Year-round training model for highly specialized volleyball athletes who participate in high school and club volleyball - Biese, K. M.; O'Leary, D.; Breunig, O.; Fregien, A.; Bunn, J. A. (Strength and Conditioning Journal, 2026)
The increased practice of sport specialization by young athletes and the plethora of competitive sport opportunities is staggering. Girls' volleyball is a sport that is experiencing high sport specialization rates and is the most popular team sport in the United States. This narrative review explored the literature surrounding girls' volleyball sport specialization, programming, and training load management in context to gathered national data on volleyball matches played throughout a calendar year. The publicly available data were collected from schools and clubs across the United States. These data provided the framework in which principals of programming for the highly specialized volleyball athletes were applied. This process created a macrocycle that starts in July and continues until the following July. This macrocycle includes both the high school and club sports and provides a suggested length and progression of the transition, preparation, precompetition, competitive, and tapering phases of mesocycles. Within each phase, recommended goals are given based on the length and training load intensity of the high school and club volleyball season. Finally, special considerations for programming club volleyball athletes are presented given the length and variability of training load during the club volleyball season for highly specialized volleyball players.